Diagnóstico de movilidad sostenible en ciudades intermedias: caso de estudio Tunja (Colombia). (Revista de Diavulgación L'esprit Ingénieux, 2025)
The present research aims to provide a diagnosis of the state of sustainable mobility between the years 2015-2023 and offer possible solutions to encourage the use of sustainable mobility as a means of transportation. This document seeks to raise awareness among the public about the importance of implementing sustainable mobility as an everyday mode of transportation.The objective is to propose potential solutions to promote environmentally friendly transportation options that help reduce environmental pollution, such as public urban transport, cycling, pedestrian modes, and micro-mobility. Furthermore, a thorough review of documents related to sustainable mobility from 2015 to 2023 will be conducted, along with an examination of plans that have been developed in the city of Tunja.Interviews with individuals knowledgeable about the subject and surveys of a sample of the population will also be carried out to analyze the public's perception of sustainable mobility. Finally, with this information, the aim is to provide a detailed analysis of survey results and offer a diagnosis of sustainable mobility in the city of Tunja for the year 2023.
Keywords: Intermediate Cities; Mobility; Sustainable mobility; Modes of transport